Reconciliation into Chinese American Culture in The Woman Warrior by Maxine Kingston: an In-depth Study of the Characters - MECHEGGUEG ,Amel; ARIBI, Brahim (Faculty of Letters and Foreign Languages Department of English, 2017)
The Chinese American literature is a very fruitful field of study. It shares many themes with the other minor and Diaspora literature like racism, sexism and the quest for identity, but it presents its originality through the writing style, techniques and the reflection of the Chinese culture, which is rich with superstitions and unique traditions. One of the masterpieces in Chinese American literature is The Woman Warrior by the contemporary writer Maxine Hong Kingston, which exposes stories told to the narrator by her mother. This research aims to shed light on the cultural confusion the writer went through in her life as it is presented in this book. In addition, it explains how Kingston‟s position as a hyphenated writer is always present all along her work. This thesis also goes thoroughly to analyze each character separately(qualitative research) to show the way Kingston reconciliates both her present American culture and the Chinese culture transmitted by her mother through storytelling to reconstitute her own. In other words, how she reaches a sense of the self and accepted her hybrid culture and identity.